2018
DOI: 10.1111/ped.13537
|View full text |Cite
|
Sign up to set email alerts
|

Mortality and short‐term morbidity in infants with exomphalos

Abstract: Infants with exomphalos regardless of size can have chronic morbidity. Mortality is commonest in those with exomphalos major born at lower gestational age and birthweight.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 13 publications
0
7
0
Order By: Relevance
“…An overall mortality of 14-30% has been reported [3,4,9,11,14]. In cases of isolated omphalocele, survival rate can be as high as 90% [9,15].…”
Section: Introductionmentioning
confidence: 99%
“…An overall mortality of 14-30% has been reported [3,4,9,11,14]. In cases of isolated omphalocele, survival rate can be as high as 90% [9,15].…”
Section: Introductionmentioning
confidence: 99%
“…Only a few population‐based studies have investigated early childhood mortality in omphalocele (Deng et al, 2014; Hijkoop et al, 2019; Marshall et al, 2015; Springett et al, 2014). Most studies conducted to date focused on clinical populations and inpatient mortality with a small numbers of cases (Akinkuotu et al, 2015; Conner et al, 2018; Corey et al, 2014; Fratelli et al, 2007; Raymond et al, 2018; Sakonidou, Ali, Farmer, Hickey, & Greenough, 2018). One USA study pooled data from several birth‐defect registries and reported infant mortality rates (Marshall et al, 2015), early and late neonatal mortality was studied in Europe (Groen et al, 2017), and a study from China reported perinatal mortality rates using data from a single registry (Deng et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…A multivariable logistic regression model was then constructed to identify whether markers of RV function and pulmonary pressure were independently associated with death. This model also included previously reported factors associated with mortality and adverse cardiac function including gestational age at birth 26 and GO. 3,26 Indeed, gestational age and GO status may be associated with outcome of death and exposure status (PH or RV dysfunction), and as such were considered as important confounders.…”
Section: Discussionmentioning
confidence: 99%
“…This model also included previously reported factors associated with mortality and adverse cardiac function including gestational age at birth 26 and GO. 3,26 Indeed, gestational age and GO status may be associated with outcome of death and exposure status (PH or RV dysfunction), and as such were considered as important confounders. Statistical analyses were done with Stata SE (Version 14.2, College Station, TX) and R (Version 3.4.4)/ RStudio (Version 1.0.143).…”
Section: Discussionmentioning
confidence: 99%